STUDI PERBANDINGAN AVALANCHE EFFECT PADA ALGORITMA KRIPTOGRAFI TRANSPOSISI UNTUK MENINGKATKAN KEAMANAN DATA - Noviyantono, Endyk; Fadlan, Muhammad; Muhammad; Suprianto (Jurnal INSYPRO (Information System and Processing), 2024)
Various cryptographic techniques have been used as a solution to maintain data security, one of which is the transposition technique which is included in the classic type of cryptography. This research aims to conduct a comparative study of two classic transposition techniques, namely Route Transposition and Rail Fence Transposition. Apart from that, this research aims to find out whether various classical transposition techniques are still relevant in the process of securing data in the current cyber era. In this research, comparative analysis was carried out based on the Avalanche Effect (AE) value. The research results show that the route transposition technique has the highest value compared to the rail fence transposition technique. However, based on the minimum standard AE value, it shows that the two techniques are still in a position below the minimum AE value, namely below 50%.